Hukum Islam Antara Idealisme Dan Realitas - Sulis Tyaningsih; Yurna Yurna (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The study discussed in this study is a library study that seeks to present descriptively with methods of qualitative and library research, i.e. library-based research, in the process of data collection, researchers conduct research and analyze library sources obtained from the theories of literary books. (library research). The result of the study of the library obtained there was a gap between the desired idealism and the reality in its implementation; 1) Islamic law idealism offers principles that are fair, fair, and based on Islamic moral values. However, in the reality of its implementation, there are challenges that result in the gap between such idealism and reality. Factors such as varied social, political, cultural, and interpretation of Islamic teachings affect the gap between idealism and the reality of the Islamic law. These factors can hinder the implementation that corresponds to the desired idealism. 3) The impact of the gap between idealism and the reality of Islamic law is visible in societies, where there is sometimes an inconsistency between public expectations of fair implementation and realities that do not meet those expectations. This can lead to dissatisfaction, injustice, and social tension. 4) To overcome this gap, efforts involving various parties are needed, including religious leaders, Islamic law scholars, legal practitioners, and the general public. In this regard, a deeper understanding of Islamic teachings, the strengthening of justice institutions, the involvement of society in the process of law-making, and the promotion of dialogue and understanding between groups can be effective measures. Building understanding and cooperation between religious leaders, Islamic law scholars, and legal practitioners with the general public is key in strengthening the implementation of Islamic Law in accordance with desired idealism. It is essential for the implementation of Islamic law to justice, sustainability, and well-being for society.